Unveiling Limestone Orchid Hotspots In The Karst Hills Of Northern Peninsular Malaysia - Bakar, Shahrul Nizam Abu (2024)
A significant knowledge gap remains regarding the diversity of orchids in the limestone hills of northern Peninsular Malaysia, especially in Kedah and Perak. Addressing this knowledge gap requires thorough comprehensive assessments and proper documentations of orchid diversity and endemism in this unique karst habitat. To fulfill this, 10 field assessments have been carried out between Mac 2021 to November 2022 to five selected limestone hills in Kedah and Perak state boundary, aimed to assess the diversity of limestone orchids and their species richness, evaluating the threats facing by the orchids and their natural habitat, determining areas with high diversity hotspots, and proposing new conservation status for the rare and endangered orchid species with restricted distribution and small population size. A total of 134 orchid species represented in 68 genera have been recorded from Gunung Batu Putih, Gunung Pong, Gunung Baling, Gunung Pulai and Gunung Fakir Terbang. From the five limestone hills, Gunung Batu Putih was known to have the most richest and diverse orchid species with a total of 105 species from 58 genera (H’ = 4.504 and D = 0.9875), followed by Gunung Pong with 103 species from 57 genera (H’ = 4.471 and D = 0.9867), Gunung Baling with 93 species from 50 genera (H’ = 4.366 and D = 0.9853), Gunung Pulai with 90 species from 49 genera (H’ = 4.296 and D = 0.9838) and lastly Gunung Fakir Terbang with 67 species from 29 genera (H’ = 3.88 and D = 0.9756). From the account, 36 species are recognized as new records to Kedah and three species as new records to Peninsular Malaysia, namely Anoectochilus sanguineus P.T.Ong & P.O’Byrne, Bulbophyllum meson J.J.Verm., Schuit. & de Vogel and Luisia brachystachys (Lindl.) Blume. Three species endemic to Peninsular Malaysia were gathered in this study which are Anoectochilus sanguineus, Cheirostylis goldschmidtiana Schltr. and Phalaenopsis appendiculata Carr. This study has also revealed the relationships between the diversity of orchids and the influences of certain environmental factors. Only soil pH and relative humidity (RH) were found to be positively correlated with orchid’s species richness. The analysis on species distribution data has shown that Gunung Batu Putih to have the highest number of hotspot areas followed by Gunung Pong, Gunung Baling, Gunung Pulai and Gunung Fakir Terbang. New conservation status have been proposed to the selected rare and endangered orchids, which four species were proposed as Critically Endangered (CR) (Aerides krabiensis, Anoectochilus albolineatus, Goodyera hispida and Phalaenopsis appendiculata), and four as Endangered (EN) (Anoectochilus sanguineus, Cheirostylis goldschmidtiana, Paphiopedilum niveum and Spathoglottis hardingiana).